The teaching of entrepreneurship in courses of management: a comparative study at State Universities of Londrina and Maringa - Vieira, Saulo Fabiano Amâncio; Melatti, Gerson Antonio; Ribeiro, Paula Regina (Revista de Administração da UFSM, 2011)
The importance of the entrepreneurship in economic and social development is verified currently with the necessity of constructing an enterprising society. An effective way is through education, that can stimulate and develop in the pupils necessary abilities and capacities to the management of an enterprise. The effective learning of disciplines of Entrepreneurship depends on the adoption of specific practical and methods of education, and not more than the models of the traditional education. Thus, this work has as objective to understand the education of entrepreneurship in public institutions of superior education of the south of the country, analyzing, among others aspects, the academic profile of the coordinators of the course of Administration and the didactic-pedagogical practices used for the education of discipline of entrepreneurship. This work is a qualitative research, presented in the form of a comparative study enters the state universities of Londrina and Maringá, both located in the Paraná. Among others aspects, the results point the trend of curricular adaptation to the new academic and market necessities, followed of the lack in the support to pedagogical practices turned to the entrepreneurship.